Menuju Era Akta Lelang Digital: Legalitas dan Tantangan Digitalisasi Minuta Risalah Lelang di Indonesia - Rita Kartika Jayanti (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The transformation of the auction process in Indonesia is now entering the digital era with the issuance of Minister of Finance Regulation (PMK) number 122 of 2023 concerning Guidelines for Auction Implementation. This PMK allows the creation and storage of quotations/grosse/copies of auction minutes electronically. The rapid development of digitalization makes the concept of digital auction minutes very feasible in the future. However, this concept raises issues due to the absence of specific regulations governing electronic minutes and the prevention of cyber crimes, which contradicts Article 5 paragraph (4) of the ITE Law and the role of notaries who are also class II auction officials, as it contradicts the UUJN. A normative juridical approach is used to analyze the legality and evidentiary strength of digital auction minutes. This approach examines existing regulations and applicable legal principles to assess whether the current regulations are adequate for implementing the concept of digital auction minutes. The research results indicate that without more specific regulations, there is a risk that the creation and storage of digital auction minutes could be legally questioned and potentially lose their perfect evidentiary strength in court. Therefore, comprehensive regulations are needed to ensure the security and validity of digital auction minutes, in order to support the digital transformation of the auction process in Indonesia. Keywords: Auction Officer; digital transformation; legality; Digital Auction Deed